Kerk en samelewing: ’n Christelik-filosofiese besinning - Walt, Barend Johannes van der (Koers, 2005)
Church and society: a Christian-philosophical reflection The problem to be discussed is the role of the church in society. In spite of the fact that this was a topical issue throughout centuries, it has today – especially because of the increasing secularisation of the social environment – become a burning issue. It seems as if churches are becoming more and more marginalised, as if they have lost their relevance for broader societal life. This article, however, indicates that a major reason for the situation may be with the churches themselves, viz. a wrong conception about their own identity. From a Biblical-Reformational perspective this wrong view is first explained historically. It is followed by a systematic exposition of the church as a societal relationship. Such a Christian-philosophical analysis in no way harms, but rather enhances the uniqueness of the church. According to this philosophy of society the church no longer needs to be irrelevant. The contribution is concluded by indicating, on the one hand, how the church should not be involved in societal life and, on the other hand, how it should correctly be related to the other aspects of life.